2019
DOI: 10.1136/bmjopen-2018-024043
|View full text |Cite
|
Sign up to set email alerts
|

Can the Easter break induce a long-term break of exercise routines? An analysis of Danish gym data using a regression discontinuity design

Abstract: ObjectivesMany sedentary individuals are aware of the health benefits of regular physical activity and start becoming more physically active. Yet, despite good intentions, many struggle to keep up initial exercise levels and experience a decline in exercise frequency. A possible explanation is that it is hard to establish habits or routines, and that such routines—once established—might be easy to break. In this paper, we analyse whether a break in habitual/routine behaviour—induced by the Easter holidays—resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…These results are in line with the idea that a context change can disrupt existing habits (Verplanken & Wood, 2006). Nevertheless, while previous studies only indirectly inferred PA habits' disruption through changes in behaviours (Fredslund & Leppin, 2019;Wood et al, 2005), our study is the first to provide a formal test of this assumption by assessing habits both before and after a context change. By contrast, an increase in PA habits was observed among individuals with weak before-lockdown habits.…”
Section: Comparisons With Other Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in line with the idea that a context change can disrupt existing habits (Verplanken & Wood, 2006). Nevertheless, while previous studies only indirectly inferred PA habits' disruption through changes in behaviours (Fredslund & Leppin, 2019;Wood et al, 2005), our study is the first to provide a formal test of this assumption by assessing habits both before and after a context change. By contrast, an increase in PA habits was observed among individuals with weak before-lockdown habits.…”
Section: Comparisons With Other Studiessupporting
confidence: 89%
“…Yet, for PA habits, this hypothesis has received little empirical support (Gardner, 2015). Only two studies have provided indirect support to the discontinuity hypothesis by showing a decrease in PA behaviours after holidays (Fredslund & Leppin, 2019) or after a move to university (Wood et al, 2005). However, PA habits were not directly assessed, thereby preventing the assessment of how habits evolved following a context change.…”
Section: Lockdownmentioning
confidence: 99%
“…Of the 76 papers [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ,…”
Section: Resultsunclassified
“…Although researchers have identified habitual action as a long-lasting process that is wellsuited for promoting behavioral maintenance (Strack & Deutsch, 2004;Wood & Neal, 2007), it should be noted that cue-response relationships can be disrupted and are not impervious to short or long-term contextual changes. For example, working adults who go on vacation have their gym attendance habit disrupted post-vacation (Fredslund & Leppin, 2019). Additionally, Acland and Levy (2015) found that university students' exercise habits were disrupted by a midsemester break.…”
Section: Habits and Behavioral Maintenancementioning
confidence: 99%
“…Additionally, identity is likely a protective factor for individuals with exercise habits who experience short-or long-term changes in their context or context stability (such as when transitioning to a new house or job or when going on vacation). These short-and long-term changes have been shown to make habitual behaviors more difficult to sustain (e.g., Fredslund & Leppin, 2019;Wood et al, 2005).…”
Section: Context Stabilitymentioning
confidence: 99%